2013
DOI: 10.1002/bmc.3025
|View full text |Cite
|
Sign up to set email alerts
|

An LC‐MS/MS method for determination of curculigoside with anti‐osteoporotic activity in rat plasma and application to a pharmacokinetic study

Abstract: A rapid, simple, selective and sensitive LC-MS/MS method was developed for the determination of curculigoside in rat plasma. The analytical procedure involves extraction of curculigoside and syringin (internal standard, IS) from rat plasma with a one-step extraction method by protein precipitation. The chromatographic resolution was performed on an Agilent XDB-C18 column (4.6 × 50 mm, 5 µm) using an isocratic mobile phase of methanol with 0.1% formic acid and H2 O with 0.1% formic acid (45:55, v/v) at a flow r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 14 publications
1
9
0
Order By: Relevance
“…These results suggested that its bioavailability was independent of the doses. A recent study [9] reported that the absolute bioavailability of curculigoside was 1.27% in rats after oral administration at dose of 32 mg/kg. Therefore, it was also concluded that curculigoside might have a low absolute bioavailability.…”
Section: Concentrationmentioning
confidence: 98%
See 1 more Smart Citation
“…These results suggested that its bioavailability was independent of the doses. A recent study [9] reported that the absolute bioavailability of curculigoside was 1.27% in rats after oral administration at dose of 32 mg/kg. Therefore, it was also concluded that curculigoside might have a low absolute bioavailability.…”
Section: Concentrationmentioning
confidence: 98%
“…Recently, an HPLC-MS/MS method has been developed to determine curculigoside in plasma and applied to pharmacokinetic study on rats [9]. However, the absorption characteristics, oral bioavailability and tissue distribution of curculigoside in vivo have not been investigated in detail.…”
Section: Introductionmentioning
confidence: 99%
“…Curculigoside (2 mg/mL) was dissolved in normal saline containing 0.5% methylcellulose and orally administered to rats at a dose of 20 mg/kg (Zhao et al 2014). The pretreated groups received oral verapamil (10 mg/kg) 30 min prior to curculigoside (Zhang et al 2015a(Zhang et al , 2015b.…”
Section: In Vivo Pharmacokinetic Studymentioning
confidence: 99%
“…There are several reasons for the poor bioavailability of a compound in the body, such as the low solubility and dissolution rate, poor permeability in intestine and fast elimination rate Shen et al 2015;Zhang et al 2015aZhang et al , 2015b. Several studies have been conducted to investigate the pharmacokinetic profiles of curculigoside in rats, and the results indicated that the oral bioavailability of curculigoside was poor (1-2%) (Zhao et al 2014;Yuan et al 2015). However, to the best of our knowledge, little information is available for the absorption and metabolic stability profiles of curculigoside, and the reason for its poor bioavailability.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation